Cartilage polymers: From viscoelastic solutions to weak gels. Issue 2 (26th August 2021) - Horkay, Ferenc; Douglas, Jack F.
Abstract: The dynamic properties of the polymeric components of cartilage are important for understanding the many biological functions of this biological tissue. Knowledge of the rheology of these materials is also crucial for the development of therapeutic treatments for diseases, such as arthritis, in which cartilage loses its functional physiological properties. In the present work complementary noninvasive techniques, rheology and dynamic light scattering (DLS) are used to probe the structural and dynamic properties of solutions of the principal proteoglycan components of cartilage extracellular matrix at different levels of structural hierarchy (chondroitin sulfate, aggrecan, aggrecan‐hyaluronic acid complex). It is shown that the bottlebrush shaped aggrecan molecules form large, loosely organized polyelectrolyte domains comprised of molecules organized into diffuse branched polymer network structures permeated by a diffuse cloud of counter‐ions. The rheological behaviors of these polymer solutions vary from viscoelastic solutions, consistent with the formation of dynamic polymer clusters in solution, to "weak gel" materials exhibiting approximate power law shear stress relaxation or creep over a wide range of timescales. Abstract : Aggrecan bottlebrush (left) and aggrecan‐HA complexes enmeshed in the collagen matrix in cartilage (right).